2022
DOI: 10.3389/fimmu.2021.752466
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3α/β Activity Negatively Regulates MMP-1/9 Expression to Suppress Mycobacterium tuberculosis Infection

Abstract: Tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) infection is the deadliest infectious disease and a global health problem. Macrophages (Mφs) and neutrophils that can phagocytose Mtb represent the first line of immune response to infection. Glycogen synthase kinase-3α/β (GSK-3α/β) represents a regulatory switch in host immune responses. However, the efficacy and molecular mechanisms of how GSK-3α/β interacts with Mtb infection in Mφs remain undefined. Here, we demonstrated that Mtb infection downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…Some studies have found that inhibiting the expression of MMP-1/9 inhibits M. tuberculosis infection [20]. However, among the DEGs induced by BCG screened in this study, we observed no differential expression of the above five isoforms.…”
Section: Discussioncontrasting
confidence: 76%
“…Some studies have found that inhibiting the expression of MMP-1/9 inhibits M. tuberculosis infection [20]. However, among the DEGs induced by BCG screened in this study, we observed no differential expression of the above five isoforms.…”
Section: Discussioncontrasting
confidence: 76%
“…Nevertheless, opposite to that which was commonly observed for cytokines and chemokines [ 41 , 42 , 43 ], the inhibition of mTOR signaling tended to upregulate the expression of MMPs. In fact, it was recently described that the attenuation of mTOR in THP-1 macrophages by rapamycin or silica dust induced the expression of relevant metalloproteinases, such as MMP1 and MMP9 [ 44 , 45 ]. Consistently with this, the exacerbation in the induction of a well-defined detrimental factor such as MMP12 by the activation of AMPK is rather unexpected, since the upregulation of this pathway typically counteracts excessive inflammatory responses in macrophages by mediating the effects of anti-inflammatory cytokines or inhibiting the production of pro-inflammatory mediators such as TNF-α and IL6 [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in human chondrosarcoma cells and articular chondrocytes, IL-1β and TNF-α have been found to increase MMP-1 expression. 40 In another scenario, mechanical stretch has been shown to induce MMP-1 expression in human keratoconus fibroblasts, highlighting its significance in corneal extracellular matrix remodeling. 41 Furthermore, upregulation of MMP-1 has been observed in Mycobacterium tuberculosis-infected macrophages, where MMP-1 appears to promote M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%